MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI POKOK VOLUME KUBUS DAN BALOK MELALUI PENDEKATAN KONTEKSTUAL KELAS V SD NEGERI 2 LABALAWA - Kaif, Sitti Hermayanti (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to "Improve student learning outcomes on the subject matter of the volume of cubes and blocks through a contextual approach to the fifth grade of SD Negeri 2 Labalawa". This research is classroom action research (CAR) in 3 cycles, each cycle includes: planning stage, action implementation stage, observation stage and reflection stage. The subjects of this study were fifth grade students of SD Negeri 2 Labalawa in the 2020/2021 academic year totaling 25 students consisting of 11 male students and 14 female students. Based on the results of actions, observations, evaluations and reflections in each cycle, it can be concluded that through a contextual approach, the learning achievement of fifth graders at SD Negeri 1 Topa on the subject of cube and cuboid volumes can be improved. This can be seen from the increase in student learning outcomes who experienced completeness, namely in the first cycle as much as 45.94%, the second cycle as much as 64.86% increased to 89.18% in the third cycle. Teacher activity has increased, namely in the first cycle as much as 72.91%, the second cycle 77.77% in the good category and in the third cycle 91.66% in the very good category. Student activity has increased, namely in the first cycle as much as 60.41%, in the second cycle 73.95% in the good category and in the third cycle 86.45% in the very good category.